Interleukin 10 Polymorphisms and Cervical Cancer Risk: A Meta-Analysis. Issue 1 (1st January 2013) - Ni, Jing; Ye, Yang; Teng, Fang; Wu, Qiang
Abstract : Background: A debate exists about whether interleukin 10 (IL-10) polymorphisms (IL-10−1082G/A and IL-10−592C/A) confer additional risk for cervical cancer. To derive a more precise estimation of the relationship between IL-10 polymorphisms and cervical cancer risk, we conducted a meta-analysis of all available studies relating the −1082G/A and −592C/A polymorphisms of the IL-10 gene to the risk of developing cervical cancer. Methods: Eight studies were eligible for IL-10 −1082G/A (1498 cases and 1608 controls), and 5 studies were eligible for IL-10 −592C/A (2396 cases and 1388 controls). Pooled odds ratios (ORs) were appropriately derived from fixed-effects or random-effects models. Subgroup analyses were performed by ethnicity and Hardy-Weinberg equilibrium in the controls. Results: In the overall analysis, no significant association between the IL-10−1082G/A polymorphism and the risk of cervical cancer was observed. In the subgroup analysis by ethnicity, IL-10 −1082A allele was associated with decreased cervical cancer susceptibility among whites (A vs G: OR, 0.39; 95% confidence interval [CI], 0.32–0.47). Studies with controls deviated from Hardy-Weinberg equilibrium showed an evident association in dominant model (GA/AA vs GG: OR, 1.73 [95% CI, 1.04–2.89]). On the other hand, with respect to −592C/A polymorphism, significantly elevated cervical cancer risk was found in the overall analysis (A vs C: OR, 1.16 [95% CI, 1.04–1.31]; AA vs CC: OR, 1.36 [95% CI, 1.00–1.84]; CA/AA vs CC: OR, 1.18 [95% CI, 1.01–1.39]; AA vs CC/CA: OR, 1.25 [95% CI, 1.01–1.55]). Stratified analysis indicated that significantly increased risks were also found among Asians in the allelic model (A vs C: OR, 1.23 [95% CI, 1.01–1.49]). Conclusions: Interleukin 10−1082 G/A polymorphism showed no effect on cervical cancer risk in the overall analysis. The genetic polymorphism in IL-10−592C/A is a risk factor for developing cervical cancer, especially for Asians.